Sedum kamtschaticum Exerts Hypnotic Effects via the Adenosine A2A Receptor in Mice - Kim, Yeon Soo; Lee, Bo Kyung; Kim, Cha Soon; Lee, Young Seob; Lee, Yoon Ji; Kim, Kwan Woo; Lee, Dae Young; Jung, Yi Sook (Nutrients, 2024)
Insomnia is a common sleep disorder with significant societal and economic impacts. Current pharmacotherapies for insomnia are often accompanied by side effects, necessitating the development of new therapeutic drugs. In this study, the hypnotic effects and mechanisms of Sedum kamtschaticum 30% ethanol extract (ESK) and one of its active compounds, myricitrin, were investigated using pentobarbital-induced sleep experiments, immunohistochemistry (IHC), receptor binding assays, and enzyme-linked immunosorbent assay (ELISA). The pentobarbital-induced sleep experiments revealed that ESK and myricitrin reduced sleep latency and prolonged total sleep time in a dose-dependent manner. Based on c-Fos immunostaining, ESK, and myricitrin enhanced the GABAergic neural activity in sleep-promoting ventrolateral preoptic nucleus (VLPO) GABAergic. By measuring the level of GABA released from VLPO GABAergic neurons, ESK and myricitrin were found to increase GABA release in the hypothalamus. These effects were significantly inhibited by SCH. Moreover, ESK exhibited a concentration-dependent binding affinity for the adenosine A2A receptors (A2AR). In conclusion, ESK and myricitrin have hypnotic effects, and their underlying mechanisms may be related to the activation of A2AR.
Keywords: Animals; Flavonoids; GABAergic Neurons; gamma-Aminobutyric Acid; Hypnotics and Sedatives; Male; Mice; Pentobarbital; Plant Extracts; Preoptic Area; Receptor, Adenosine A2A; Sleep; Sleep Initiation and Maintenance Disorders; adenosine A2A receptor; GABAergic neuron; hypnotic effect; myricitrin; Sedum kamtschaticum